Chemical Composition of Pterospermum heterophyllum Root and its Anti-Arthritis Effect on Adjuvant-Induced Arthritis in Rats via Modulation of Inflammatory Responses - Yang, Li; Liu, Ronghua; Fan, Aiguo; Zhao, Jingjing; Zhang, Yong; He, Junwei (Frontiers in Pharmacology, 2020)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease without effective and beneficial drugs. Many traditional folk medicines have been proven to be effective in treating RA. Among these, the root of Pterospermum heterophyllum Hance has been widely used as a traditional remedy against RA in China, but there is no scientific basis yet. The aim of this study was to investigate for the first time the chemical compositions and therapeutic effect of P. heterophyllum on adjuvant-induced arthritis (AIA) model in rats. 73 compounds were identified from P. heterophyllum based on ultra-performance liquid chromatography-quadrupole time-of-flight tandem mass spectrometry (UPLC-qTOF-MS/MS), and flavonoids may be partly responsible for the major anti-arthritic effect. In parallel, the P. heterophyllum extract at 160, 320, and 640 mg/kg/day were orally administered to rats for 22 days after post-administration adjuvant. The results showed that P. heterophyllum remarkably ameliorated histological lesions of the knee joint, increased body weight growth, decreased arthritis score, reduced thymus and spleen indices in model rats. Moreover, P. heterophyllum treatment persuasively downregulated the levels of rheumatoid factor (RF), C-reactive protein (CRP), tumor necrosis factor alpha (TNF-α), interleukin-1β (IL-1β), IL-6, IL-17, cyclooxygenase-2 (COX-2), 5-lipoxygenase (5-LOX) and matrix metalloproteinase-2 (MMP-2), and observably upregulated IL-4 and IL-10 levels in model rats. These findings suggest that P. heterophyllum has a prominent anti-RA effect on AIA rats by modulating the inflammatory responses, and supports the traditional folk use of this plant.